2023
DOI: 10.1063/5.0143875
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of specific heat and thermal conductivity in pulsed magnetic fields

Abstract: We report an experimental setup for simultaneously measuring specific heat and thermal conductivity in feedback-controlled pulsed magnetic fields of 50 ms duration at cryogenic temperatures. A stabilized magnetic field pulse obtained by the feedback control, which dramatically improves the thermal stability of the setup and sample, is used in combination with the flash method to obtain absolute values of thermal properties up to 37.2 T in the 22–16 K temperature range. We describe the experimental setup and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…By analysing conductive non-magnetic materials [11], it was found that in the system in Figure 2a, it is possible to use the modified Flash method [12][13][14][15][16][17] to estimate the thermal diffusivity of a cylindrical sample of the tested material. The application of the Flash method in the considered inductor-charge system consisted of implementing, using the system from Figure 2c, excitation in the form of short 20 or 10 millisecond pulses of the inductor current with a frequency of f = 40 kHz and RSM values of I = 1100 and 1550A, respectively.…”
Section: Using the Impulse Methods To Estimate The Thermal Diffusivit...mentioning
confidence: 99%
See 1 more Smart Citation
“…By analysing conductive non-magnetic materials [11], it was found that in the system in Figure 2a, it is possible to use the modified Flash method [12][13][14][15][16][17] to estimate the thermal diffusivity of a cylindrical sample of the tested material. The application of the Flash method in the considered inductor-charge system consisted of implementing, using the system from Figure 2c, excitation in the form of short 20 or 10 millisecond pulses of the inductor current with a frequency of f = 40 kHz and RSM values of I = 1100 and 1550A, respectively.…”
Section: Using the Impulse Methods To Estimate The Thermal Diffusivit...mentioning
confidence: 99%
“…The rest of the article initially presents brief information about the measurement station and the simulation analysis methods used. The method of using the modified Flash method [12][13][14][15][16][17] for the measurement of thermal diffusivity at an induction heating measurement station was presented, and the possibilities of measuring the volumetric heat capacity of ferromagnetic materials using the same measurement station were analysed. The influence of resistivity and magnetic permeability on the tested electrical parameters of the measurement system is discussed, and the possibilities of distinguishing the influence of each of these properties individually are indicated.…”
Section: Introductionmentioning
confidence: 99%
“…Only the procedure of heating and measuring the temperature response of the charge was changed here. For the measurement of thermal diffusivity, use of the modified Flash method [10][11][12][13][14] was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Only the procedure of heating and measuring the temperature response of the charge was changed here. For the measurement of thermal diffusivity, use of the modified Flash method [10][11][12][13][14] was proposed. The classic Flash method consists of directing a pulse of electromagnetic radiation (from a radiator or a laser) of a character as close as possible to the Dirac pulse at the base of the cylindrical charge and recording, in the time domain, the temperature on the opposite side.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation